Adhesive Materials Inspired by Barnacle Underwater Adhesion: Biological Principles and Biomimetic Designs - Gan, Kesheng; Liang, Chao; Bi, Xiangyun; Wu, Jizhe; Ye, Zonghuang; Wu, Wenjian; Hu, Biru (Frontiers in Bioengineering and Biotechnology, 2022)
Wet adhesion technology has potential applications in various fields, especially the biomedical field, yet it has not been completely mastered by humans. Many aquatic organisms (e.g., mussels, sandcastle worms, and barnacles) have evolved into wet adhesion specialists with excellent underwater adhesion abilities, and mimicking their adhesion principles to engineer artificial adhesive materials offers an important avenue to address the wet adhesion issue. The crustacean barnacle secretes a proteinaceous adhesive called barnacle cement, with which they firmly attach their bodies to almost any substrate underwater. Owing to the unique chemical composition, structural property, and adhesion mechanism, barnacle cement has attracted widespread research interest as a novel model for designing biomimetic adhesive materials, with significant progress being made. To further boost the development of barnacle cement-inspired adhesive materials (BCIAMs), it is necessary to systematically summarize their design strategies and research advances. However, no relevant reviews have been published yet. In this context, herein we presented a systematic review for the first time. Firstly, we introduced the underwater adhesion principles of natural barnacle cement, which lay the basis for the design of BCIAMs. Subsequently, we classified the BCIAMs into three major categories according to the different design strategies and summarized their research advances in great detail. Finally, we discussed the research challenge and future trends of this field. We believe that this review can not only improve our understanding of the molecular mechanism of barnacle underwater adhesion but also accelerate the development of barnacle-inspired wet adhesion technology.